ANALISIS KESALAHAN MENULIS PENGGUNAAN HURUF KAPITAL DAN TANDA BACA PADA SISWA KELAS II SDN KERONCONG 1 - Khofifah Puspa Lestari; Erdhita Oktrifianty; Yayah Huliatunisa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study was conducted to determine the types of errors frequently made by second-grade students of SDN Keroncong 1 in using capital letters and punctuation when writing. Based on initial observations, many students still write without paying attention to correct writing rules, such as capitalizing at the beginning of a sentence or in people's names, and frequently skipping punctuation marks such as periods and commas. This study used a descriptive qualitative approach with data collection techniques including written tests, observations, interviews, and documentation. The results showed that most students were inconsistent in their use of capital letters and punctuation, especially in simple sentences. Influencing factors included a lack of understanding of spelling rules, limited practice in correct writing, and suboptimal teaching strategies in the classroom. These findings are expected to assist teachers in evaluating writing instruction and placing greater emphasis on spelling and punctuation, so that students' writing skills gradually improve.